Determination Levels of Caffeine Isolated from Robusta Coffee Beans from Pagar Alam in Wistar Rat Blood - Yunida Yunida; Muhammad Totong Kamaluddin; Theodorus Theodorus; Sonlimar Simangunsong (Biomedika, 2022)
Coffee provides a genuine source of caffeine. Caffeine can have a variety of pharmacological effects on both central and peripheral nervous systems and most of these effects are related to the antagonistic mechanism at adenosine receptors. The most prominent effect of caffeine remains stimulation of brain function, improving mood and physical performance. Robusta coffee obtains an intense level of caffeine and Pagar Alam City is one of the cities in Indonesia that produces robusta coffees. This study aims to identify and characterize caffeine isolated from Pagar Alam robusta coffee beans using thin-layer chromatography methods, UV-Visible spectrophotometry and to determine caffeine levels in wistar rat blood using the ELISA method. This method is cost-effective, familiar to perform and has a considerable degree of accuracy and reproducibility. The isolated samples have similar characteristics to standard caffeine with an Rf value of 0.77, a maximum wavelength at 273 nm with the absorbance of 1.3 and from caffeine profile in the blood sample we obtained the maximum sample concentration in blood 0.582 ± 0.249 μg/ml and the time needed to reach the maximum concentration is 30 minutes.